2015
DOI: 10.1111/1471-0528.13706
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of recommendations for pharmacologic thromboembolism prophylaxis after caesarean delivery from three major guidelines

Abstract: Recommendations from major society guidelines for post-caesarean thromboprophylaxis differ greatly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 28 publications
3
71
0
3
Order By: Relevance
“…A recent review of post-cesarean delivery patients found that 1%, 35%, and 85% of patients would receive pharmacologic prophylaxis under the ACOG, ACCP, and Royal College of Obstetricians and Gynaecologists criteria, respectfully. 11,263 In an effort to reduce the frequency of obstetric thromboembolism and improve maternal outcomes, the NPMS, a multidisciplinary working group representing all major women's health care professional organizations, has recently published a Consensus Bundle on Venous Thromboembolism. 13 The bundle advocates for more aggressive risk-based assessment of obstetric patients, which will ultimately result in not only an increased use, but also likely increased doses of antithrombotic agents.…”
Section: And the Royalmentioning
confidence: 99%
“…A recent review of post-cesarean delivery patients found that 1%, 35%, and 85% of patients would receive pharmacologic prophylaxis under the ACOG, ACCP, and Royal College of Obstetricians and Gynaecologists criteria, respectfully. 11,263 In an effort to reduce the frequency of obstetric thromboembolism and improve maternal outcomes, the NPMS, a multidisciplinary working group representing all major women's health care professional organizations, has recently published a Consensus Bundle on Venous Thromboembolism. 13 The bundle advocates for more aggressive risk-based assessment of obstetric patients, which will ultimately result in not only an increased use, but also likely increased doses of antithrombotic agents.…”
Section: And the Royalmentioning
confidence: 99%
“…Esta disparidad se puede explicar porque la evidencia para apoyar o sugerir diferentes factores de riesgo como indicativos de tromboprofilaxis no es alta (17). Un trabajo publicado por Palmerola et al, en el que se comparan tres guías con 293 pacientes sometidas a cesárea encontraron que el 85 % de las pacientes, según el RCOG, deberían recibir tromboprofilaxis, el 1 % según recomendaciones de ACOG y el 38,4 % según las guías del CHEST (18). No obstante, existe una constante en todas las guías que es importante resaltar y es la necesidad de evaluar el riesgo trombótico en todas las pacientes durante el embarazo y en el posparto inmediato (16).…”
Section: Discussionunclassified
“…Investigators have called for RCTs to evaluate postpartum LMWH prophylaxis 1, 2, 44, 68. Although RCTs have drawbacks when applied to complex phenomena, they are ideally suited to evaluate drug therapy 29, 69.…”
Section: Lessons Of Evidence‐based Medicinementioning
confidence: 99%
“…Since the magnitudes of potential benefit and harm are very small, the numbers required to achieve adequate power are daunting; however, large trials of medical and surgical patients have been conducted successfully. Using inclusion criteria from the current RCOG guideline, more than 80% of women undergoing CD would qualify 2. With CD rates exceeding 30% in some jurisdictions, this equates to more than a thousand women annually in many large maternity hospitals.…”
Section: Lessons Of Evidence‐based Medicinementioning
confidence: 99%